2012
DOI: 10.1021/bi3009399
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Motion Capture for Sphingomyelin by Site-Specific Deuterium Labeling

Abstract: Lipid rafts have attracted much attention because of their significant functional roles in membrane-associated processes. It is thought that sphingomyelin and cholesterol are essential for forming lipid rafts; however, their motion characteristics are not fully understood despite numerous studies. Here we show accurate local motions encompassing an entire sphingomyelin molecule, which were captured by measuring quadrupole splittings for 19 kinds of site-specifically deuterated sphingomyelins (that is, molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 40 publications
9
88
0
Order By: Relevance
“…The outer and inner Pake doublets correspond to the L o and L d domains, respectively (Fig. 7C) (28). The diyne-SM mixture gave a pair of Pake doublets at Δν = 48.1 kHz, which is close to the outer Pake obtained from the SM mixture (Δν = 51.9 kHz) (Fig.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The outer and inner Pake doublets correspond to the L o and L d domains, respectively (Fig. 7C) (28). The diyne-SM mixture gave a pair of Pake doublets at Δν = 48.1 kHz, which is close to the outer Pake obtained from the SM mixture (Δν = 51.9 kHz) (Fig.…”
Section: Resultssupporting
confidence: 58%
“…S9 and S10); d 2 -diyne-SM was synthesized similarly to diyne-SM, and d 2 -SM was prepared (details in Figs. S11 and S12), as reported (28). Other chemicals were purchased from Wako Pure Chemical Industries, Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…We recently synthesized site-specifically deuterated N-stearoylsphingomyelin (SSM, Fig. 1 a) and measured their quadrupole splitting in single-component SSM and binary SSM-Chol membrane systems, which revealed accurate segmental motions of methylene groups encompassing an entire SSM molecule (29,30). In this report, we further applied the site-specifically deuterated SSMs to raft-exhibiting ternary mixtures (SSM/DOPC/Chol) and acquired the quadrupole coupling profiles of SSM from L o and L d domains separately and simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, site-selectively 2 H-labeled compounds were used to avoid overlapping of quadrupole doublet signals found in perdeuterated acyl chains, 24 which can alter the physical properties of lipid bilayers as well. 25 Our previous study indicated that chol enhances the order of the C10 position more effectively than other positions in the acyl chains of SM, 15 implying that the 2 H NMR spectrum should show clearly separated signals for the L o and L d phases. However, the clear phase separation of 5 is hardly observed in liposome preparation.…”
Section: Resultsmentioning
confidence: 98%